El Liber commicus de Toledo (Bibl. Cap. 35.8). Estudi litúrgic - Gros i Pujol, Miquel dels Sants (Miscel·lània litúrgica catalana, 2022)
This paper presents a study and the text of the Liber commicus of Toledo, together with a liturgical commentary. The Liber commicus of Toledo, a lectionary that was copied in the city of Toledo in the final phase of the Hispanic liturgy, is one of the essential sources for the study of this rite.